Volatile organic compounds from entomopathogenic and nematophagous fungi repel banana weevil (Cosmopolites sordidus) under banana field conditions - Lozano-Soria, Ana; Piedra-Buena Diaz, Ana; Lopez-Moya, Federico; Valverde-Urrea, Miguel; Zubcoff, Jose J.; Martinez-Perez, Jose Emilio; Lopez-Cepero, Javier; Lopez-Llorca, Luis V. (PeerJ, 2025)
Fungal volatile organic compounds (VOCs) with biological activity produced by entomopathogenic fungi (Beauveria bassiana and Metarhizium robertsii) isolated from banana fields (Canary Islands) and the nematophagous fungus Pochonia chlamydosporia, used in biocontrol of root-knot nematodes, repel the banana weevil (BW), Cosmopolites sordidus (Germar, 1824) under laboratory conditions. BW is the main pest of banana (Musa spp. (Linnaeus, 1753)). Its cryptic behavior makes it difficult to manage. Repellent VOCs alter BW behavior and can thus be used in sustainable pest management strategies. We evaluated fungal VOCs styrene (C1), benzothiazole (C2), 1,3-dimethoxybenzene (C5) and 2-cyclohepten-1-one (C7) in Canary Islands banana fields naturally infested with BW. 1,3-dimethoxybenzene (C5) significantly reduced the attraction of BW adults to sordidin (BW aggregation pheromone) in banana fields. C5 was detected in the field using GC-MS. C1 and C2 had a mild repellent effect influenced by seasonal changes. C7 VOC did not repel BW in the field. Site and season affected VOCs repellence to BW. Climate may influence VOCs evaporation and therefore their repellent efficacy. VOCs modify BW spatial ecology under field conditions. The inverse distance weighted (IDW) interpolation technique showed changes in BW infestation patterns after application of VOCs in the field. In conclusion, VOCs from biocontrol fungi reduced BW attraction to its aggregation pheromone in banana fields. These responses to experimental BW repellents were influenced by weather and BW population size. BW repellents have potential to be used in “push-pull” strategies to manage BW sustainably in banana crops.
Keywords: Fungal VOCs; Semiochemicals; Insect repellent; Integrated pest management; Push and pull